Convocações ecológicas: o meio ambiente nas campanhas presidenciais brasileiras - Aquino, Filipe (Sociologia: Revista da Faculdade de Letras da Universidade do Porto, 2021)
This article analyzes, from a sociological and semiotic point of view, the discursive constructions of the three most voted Brazilian presidential candidates, in the 2010 and 2014 elections, to understand how each discursive agenda was constructed and their choice of themes and figures who built their political personas. This investigation examined all the approaches about the environment understanding the idea of economic development communicated in the Brazilian Electoral Propagandas. It became evident with the different discursive operations that there is a low interest in ecological issues and sustainable development.